Composite phase change material adopting dual-network packaging and preparation method thereof
By using dual network packaging technology in phase change materials, RGO and crosslinked SA are used to form composite materials, the problems of phase change material leakage and high cost are solved, and high thermal conductivity, good packaging and low-cost composite phase change materials are achieved.
Patent Information
- Application Number
- CN202411923030.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Existing phase change materials are prone to leakage during solid-liquid transformation, which limits their application in the fields of building energy saving, electronic equipment cooling and warm clothing. In addition, the single-network packaging method consumes a large amount of graphene, is costly and has poor thermal cycling performance.
A composite phase change material using a dual network package is formed by forming a reduced graphene oxide (RGO) of the first network under the interaction of π-π conjugation and van der Waals forces, and then a second network is formed by cross-linking sodium alginate (SA) using calcium ion to form a RGO/CA/PEG composite material.
The leakage problem of phase change materials is significantly improved, the thermal conductivity, packaging effect and thermal stability are improved, and production costs are reduced.
Smart Images

Figure BDA0005208508430000101 
Figure HDA0005208508520000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of phase change materials, and in particular relates to a composite phase change material using double network packaging, and a preparation method of the composite phase change material. Background Art
[0002] Phase change materials, as an ideal thermal energy storage material, can absorb or release heat through phase change between solid and liquid at a specific temperature. This property makes it valuable for research in the fields of building energy conservation, electronic equipment cooling and warm clothing. However, the inevitable leakage of phase change materials during the solid-liquid transition process will greatly limit its scope of use. Therefore, it is very important to choose the packaging method to form a composite phase change material with stable shape.
[0003] Graphene is a single layer of carbon atoms in sp 2 The preparation process of nanomaterials with a two-dimensional honeycomb network structure formed by the close stacking of hybrid orbitals is usually obtained by eliminating oxygen-containing functional groups using graphene oxide (GO) as a precursor. In addition, graphene sheets can form a three-dimensional network structure through self-assembly under the interaction of π-π conjugation and van der Waals forces, which makes it have good application prospects in many fields.
[0004] Using a single graphene network to encapsulate phase change materials is a common packaging method, but the formation of the network means that a large amount of expensive graphene is required, which is not conducive to its industrial production. At the same time, the composite phase change materials prepared by single network packaging often perform poorly in thermal cycling, which will limit their further application. Summary of the invention
[0005] The purpose of the present invention is to solve the above technical problems and provide a composite phase change material with double network packaging and a preparation method thereof, so that the new composite phase change material prepared by the present invention has the advantages of strong thermal conductivity, good packaging effect, strong thermal stability and low production cost.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] The composite phase change material using double network packaging includes the following components by weight:
[0008] Phase change material 100 parts;
[0009] Sodium alginate (SA) 20 parts;
[0010] Graphene oxide (GO) 1-9 parts;
[0011] L-ascorbic acid (VC) 1-9 parts;
[0012] 1 to 5 parts of thermal conductive filler;
[0013] 1 to 3 parts of nucleating agent.
[0014] Preferably, the phase change material is one of polyethylene glycol 2000 (PEG-2000), polyethylene glycol 4000 (PEG-4000), polyethylene glycol 6000 (PEG-6000), or a combination of two or more thereof.
[0015] Preferably, the viscosity of the SA is 5000 mPa·s, and the pH value of its 1% aqueous solution is 6-8.
[0016] Preferably, the GO has a thickness of 1-2 nm, a diameter of 15-20 μm, and a specific surface area of 300-350 m 2 / g, and the carbon content accounts for 51-55%.
[0017] Preferably, the VC has a molecular weight of 176.12 g / mol and a density of 1.65 g / cm at 20°C. 3 .
[0018] Preferably, the thermally conductive filler is one or a combination of two or more of aluminum oxide, aluminum nitride and silicon micropowder.
[0019] Preferably, the nucleating agent is one or a combination of two or more of sodium succinate, aluminum adipate, and sodium cinnamate.
[0020] The method for preparing the composite phase change material using dual network packaging comprises the following steps:
[0021] S1. GO was dispersed in 50 ml of deionized water, magnetically stirred at room temperature for 8 h, and then ultrasonically exfoliated at 400 W for 16 h to obtain a stable GO dispersion for use;
[0022] S2, adding phase change material, SA, GO, thermal conductive filler and nucleating agent into GO dispersion, stirring mechanically at 80°C and 500 r / min for 3 h to obtain GO / SA / PEG sol;
[0023] S3, adding VC to the above sol, stirring at room temperature until uniformly dispersed, and then placing it in a vacuum oven at 80°C for 6 hours to fully reduce GO to reduced graphene oxide (RGO) to form a first network, thereby obtaining a RGO / SA / PEG mixed sol;
[0024] S4, soaking the mixed sol in a 3wt% calcium chloride (CaCl2) solution to form a second network by cross-linking SA with calcium ions to obtain RGO / CA / PEG gel;
[0025] S5. Place the above gel in an oven at 60° C. and dry for 12 h to finally obtain the desired product.
[0026] Preferably, in S1, the GO has a thickness of 1-2 nm, a diameter of 15-20 μm, and a specific surface area of 300-350 m 2 / g, and the carbon content accounts for 51-55%.
[0027] Preferably, in S2, the phase change material is one or a combination of two or more of polyethylene glycol 2000 (PEG-2000), polyethylene glycol 4000 (PEG-4000), and polyethylene glycol 6000 (PEG-6000).
[0028] The viscosity of the SA is 5000 mPa·s, and the pH value of its 1% aqueous solution is 6-8.
[0029] The thermal conductive filler is one of aluminum oxide, aluminum nitride, and silicon micropowder, or a combination of two or more thereof.
[0030] The nucleating agent is one or a combination of two or more of sodium succinate, aluminum adipate and sodium cinnamate.
[0031] Preferably, in S3, the VC has a molecular weight of 176.12 g / mol and a density of 1.65 g / cm at 20°C. 3 .
[0032] Compared with the prior art, the composite phase change material using double network encapsulation provided by the present invention has a first network that uses two-dimensional GO sheets to reduce and self-assemble the phase change material for the first time, and then uses calcium ion cross-linking SA for secondary encapsulation to obtain reduced graphene oxide / calcium alginate / polyethylene glycol (RGO / CA / PEG) composite phase change material. RGO / CA / PEG prepared by double network encapsulation technology can not only significantly improve the leakage problem of phase change materials, but also GO is reduced in situ in SA solution by self-assembly, which can effectively prevent excessive agglomeration and accumulation between RGO, thereby giving PEG good thermal conductivity. The RGO / CA / PEG composite phase change material prepared based on double network encapsulation technology has broad application prospects in solar energy utilization and thermal management.
[0033] Performance test of composite phase change materials
[0034] The phase change enthalpy was tested using a differential scanning calorimeter. The test method was to characterize the thermal properties of the material in the temperature range of 0 to 80°C under a nitrogen atmosphere, with a heating rate of 10°C / min.
[0035] The thermal conductivity was tested using a thermal conductivity meter TC3000E. The test method was to mold the sample into a 30mm×30mm×5mm sample, then press the sample onto the sensor with a 500g weight, and after thermal equilibrium, test each sample 5 times, and take the average value of the final result.
[0036] The leakage is tested using a temperature-controlled heating platform. The temperature-controlled heating platform consists of an intelligent temperature control box MY803-H and a 1800W cast aluminum heating plate (dimensions: 300×200×20mm). The test method is to place the sample to be tested on the heating platform, raise the temperature of the heating platform to 80°C and maintain it for 30 minutes through program temperature control, and use a camera to take pictures to record the leakage. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The leakage test diagram of pure phase change material and Examples 1-5 DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is described in detail, clearly and completely in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are not used to limit the present disclosure.
[0039] [Example 1]
[0040] The present embodiment provides a composite phase change material using double network encapsulation, which includes the following components by weight: 100 parts of PEG-6000; 20 parts of SA; 1 part of GO; 1 part of VC; 3 parts of aluminum oxide; and 2 parts of aluminum adipate.
[0041] The viscosity of SA is 5000 mPa·s, and the pH value of its 1% aqueous solution is 6-8.
[0042] GO has a thickness of 1-2 nm, a diameter of 15-20 μm, and a specific surface area of 300-350 m 2 / g, and the carbon content accounts for 51-55%.
[0043] The preparation method of the composite phase change material using dual network packaging in this embodiment includes the following steps:
[0044] S1. GO was dispersed in 50 ml of deionized water, magnetically stirred at room temperature for 8 h, and then ultrasonically exfoliated at 400 W for 16 h to obtain a stable GO dispersion for use;
[0045] S2, adding phase change material, SA, GO, alumina and aluminum adipate into GO dispersion, stirring mechanically at 80°C and 500 r / min for 3 h to obtain GO / SA / PEG sol;
[0046] S3, adding VC to the above sol, stirring at room temperature until uniformly dispersed, and then placing it in a vacuum oven at 80°C for 6 hours to fully reduce GO to reduced graphene oxide (RGO) to form a first network, thereby obtaining a RGO / SA / PEG mixed sol;
[0047] S4, soaking the mixed sol in a 3wt% calcium chloride (CaCl2) solution to form a second network by cross-linking SA with calcium ions to obtain RGO / CA / PEG gel;
[0048] S5. Place the above gel in an oven at 60° C. and dry for 12 h to finally obtain the desired product.
[0049] For the convenience of comparison, the experimental results are listed in Table 1.
[0050] [Example 2]
[0051] The present embodiment provides a composite phase change material using double network encapsulation, which includes the following components by weight: 100 parts of PEG-4000; 20 parts of SA; 3 parts of GO; 3 parts of VC; 3 parts of aluminum nitride; and 2 parts of sodium cinnamate.
[0052] The viscosity of SA is 5000 mPa·s, and the pH value of its 1% aqueous solution is 6-8.
[0053] GO has a thickness of 1-2 nm, a diameter of 15-20 μm, and a specific surface area of 300-350 m 2 / g, and the carbon content accounts for 51-55%.
[0054] The preparation method of the composite phase change material using dual network packaging in this embodiment includes the following steps:
[0055] S1. GO was dispersed in 50 ml of deionized water, magnetically stirred at room temperature for 8 h, and then ultrasonically exfoliated at 400 W for 16 h to obtain a stable GO dispersion for use;
[0056] S2, adding phase change material, SA, GO, aluminum nitride and sodium cinnamate into GO dispersion, stirring mechanically at 80°C and 500 r / min for 3 h to obtain GO / SA / PEG sol;
[0057] S3, adding VC to the above sol, stirring at room temperature until uniformly dispersed, and then placing it in a vacuum oven at 80°C for 6 hours to fully reduce GO to reduced graphene oxide (RGO) to form a first network, thereby obtaining a RGO / SA / PEG mixed sol;
[0058] S4, soaking the mixed sol in a 3wt% calcium chloride (CaCl2) solution to form a second network by cross-linking SA with calcium ions to obtain RGO / CA / PEG gel;
[0059] S5. Place the above gel in an oven at 60° C. and dry for 12 h to finally obtain the desired product.
[0060] For the convenience of comparison, the experimental results are listed in Table 1.
[0061] [Example 3]
[0062] The present embodiment provides a composite phase change material using double network encapsulation, which includes the following components by weight: 100 parts of PEG-2000; 20 parts of SA; 5 parts of GO; 5 parts of VC; 3 parts of silicon micropowder; and 2 parts of sodium succinate.
[0063] The viscosity of SA is 5000 mPa·s, and the pH value of its 1% aqueous solution is 6-8.
[0064] GO has a thickness of 1-2 nm, a diameter of 15-20 μm, and a specific surface area of 300-350 m 2 / g, and the carbon content accounts for 51-55%.
[0065] The preparation method of the composite phase change material using dual network packaging in this embodiment includes the following steps:
[0066] S1. GO was dispersed in 50 ml of deionized water, magnetically stirred at room temperature for 8 h, and then ultrasonically exfoliated at 400 W for 16 h to obtain a stable GO dispersion for use;
[0067] S2, adding phase change material, SA, GO, silica powder and sodium succinate into GO dispersion, stirring mechanically at 80°C and 500 r / min for 3 h to obtain GO / SA / PEG sol;
[0068] S3, adding VC to the above sol, stirring at room temperature until uniformly dispersed, and then placing it in a vacuum oven at 80°C for 6 hours to fully reduce GO to reduced graphene oxide (RGO) to form a first network, thereby obtaining a RGO / SA / PEG mixed sol;
[0069] S4, soaking the mixed sol in a 3wt% calcium chloride (CaCl2) solution to form a second network by cross-linking SA with calcium ions to obtain RGO / CA / PEG gel;
[0070] S5. Place the above gel in an oven at 60° C. and dry for 12 h to finally obtain the desired product.
[0071] For the convenience of comparison, the experimental results are listed in Table 1.
[0072] [Example 4]
[0073] The present embodiment provides a composite phase change material using double network encapsulation, which includes the following components by weight: 100 parts of PEG-6000; 20 parts of SA; 7 parts of GO; 7 parts of VC; 3 parts of aluminum oxide; and 2 parts of aluminum adipate.
[0074] The viscosity of SA is 5000 mPa·s, and the pH value of its 1% aqueous solution is 6-8.
[0075] GO has a thickness of 1-2 nm, a diameter of 15-20 μm, and a specific surface area of 300-350 m 2 / g, and the carbon content accounts for 51-55%.
[0076] The preparation method of the composite phase change material using dual network packaging in this embodiment includes the following steps:
[0077] S1. GO was dispersed in 50 ml of deionized water, magnetically stirred at room temperature for 8 h, and then ultrasonically exfoliated at 400 W for 16 h to obtain a stable GO dispersion for use;
[0078] S2, adding phase change material, SA, GO, alumina and aluminum adipate into GO dispersion, stirring mechanically at 80°C and 500 r / min for 3 h to obtain GO / SA / PEG sol;
[0079] S3, adding VC to the above sol, stirring at room temperature until uniformly dispersed, and then placing it in a vacuum oven at 80°C for 6 hours to fully reduce GO to reduced graphene oxide (RGO) to form a first network, thereby obtaining a RGO / SA / PEG mixed sol;
[0080] S4, soaking the mixed sol in a 3wt% calcium chloride (CaCl2) solution to form a second network by cross-linking SA with calcium ions to obtain RGO / CA / PEG gel;
[0081] S5. Place the above gel in an oven at 60° C. and dry for 12 h to finally obtain the desired product.
[0082] For the convenience of comparison, the experimental results are listed in Table 1.
[0083] [Example 5]
[0084] The present embodiment provides a composite phase change material using double network encapsulation, which includes the following components by weight: 100 parts of PEG-6000; 20 parts of SA; 9 parts of GO; 9 parts of VC; 3 parts of aluminum oxide; and 2 parts of aluminum adipate.
[0085] The viscosity of SA is 5000 mPa·s, and the pH value of its 1% aqueous solution is 6-8.
[0086] GO has a thickness of 1-2 nm, a diameter of 15-20 μm, and a specific surface area of 300-350 m 2 / g, and the carbon content accounts for 51-55%.
[0087] The preparation method of the composite phase change material using dual network packaging in this embodiment includes the following steps:
[0088] S1. GO was dispersed in 50 ml of deionized water, magnetically stirred at room temperature for 8 h, and then ultrasonically exfoliated at 400 W for 16 h to obtain a stable GO dispersion for use;
[0089] S2, adding phase change material, SA, GO, alumina and aluminum adipate into GO dispersion, stirring mechanically at 80°C and 500 r / min for 3 h to obtain GO / SA / PEG sol;
[0090] S3, adding VC to the above sol, stirring at room temperature until uniformly dispersed, and then placing it in a vacuum oven at 80°C for 6 hours to fully reduce GO to reduced graphene oxide (RGO) to form a first network, thereby obtaining a RGO / SA / PEG mixed sol;
[0091] S4, soaking the mixed sol in a 3wt% calcium chloride (CaCl2) solution to form a second network by cross-linking SA with calcium ions to obtain RGO / CA / PEG gel;
[0092] S5. Place the above gel in an oven at 60° C. and dry for 12 h to finally obtain the desired product.
[0093] For the convenience of comparison, the experimental results are listed in Table 1.
[0094] [Example 6]
[0095] The present embodiment provides a composite phase change material using double network encapsulation, which includes the following components by weight: 100 parts of PEG-6000; 20 parts of SA; 7 parts of GO; 7 parts of VC; 1 part of aluminum oxide; and 2 parts of aluminum adipate.
[0096] The viscosity of SA is 5000 mPa·s, and the pH value of its 1% aqueous solution is 6-8.
[0097] GO has a thickness of 1-2 nm, a diameter of 15-20 μm, and a specific surface area of 300-350 m 2 / g, and the carbon content accounts for 51-55%.
[0098] The preparation method of the composite phase change material using dual network packaging in this embodiment includes the following steps:
[0099] S1. GO was dispersed in 50 ml of deionized water, magnetically stirred at room temperature for 8 h, and then ultrasonically exfoliated at 400 W for 16 h to obtain a stable GO dispersion for use;
[0100] S2, adding phase change material, SA, GO, alumina and aluminum adipate into GO dispersion, stirring mechanically at 80°C and 500 r / min for 3 h to obtain GO / SA / PEG sol;
[0101] S3, adding VC to the above sol, stirring at room temperature until uniformly dispersed, and then placing it in a vacuum oven at 80°C for 6 hours to fully reduce GO to reduced graphene oxide (RGO) to form a first network, thereby obtaining a RGO / SA / PEG mixed sol;
[0102] S4, soaking the mixed sol in a 3wt% calcium chloride (CaCl2) solution to form a second network by cross-linking SA with calcium ions to obtain RGO / CA / PEG gel;
[0103] S5. Place the above gel in an oven at 60° C. and dry for 12 h to finally obtain the desired product.
[0104] For the convenience of comparison, the experimental results are listed in Table 1.
[0105] [Example 7]
[0106] The present embodiment provides a composite phase change material using double network encapsulation, which includes the following components by weight: 100 parts of PEG-6000; 20 parts of SA; 7 parts of GO; 7 parts of VC; 5 parts of aluminum oxide; and 2 parts of aluminum adipate.
[0107] The viscosity of SA is 5000 mPa·s, and the pH value of its 1% aqueous solution is 6-8.
[0108] GO has a thickness of 1-2 nm, a diameter of 15-20 μm, and a specific surface area of 300-350 m 2 / g, and the carbon content accounts for 51-55%.
[0109] The preparation method of the composite phase change material using dual network packaging in this embodiment includes the following steps:
[0110] S1. GO was dispersed in 50 ml of deionized water, magnetically stirred at room temperature for 8 h, and then ultrasonically exfoliated at 400 W for 16 h to obtain a stable GO dispersion for use;
[0111] S2, adding phase change material, SA, GO, alumina and aluminum adipate into GO dispersion, stirring mechanically at 80°C and 500 r / min for 3 h to obtain GO / SA / PEG sol;
[0112] S3, adding VC to the above sol, stirring at room temperature until uniformly dispersed, and then placing it in a vacuum oven at 80°C for 6 hours to fully reduce GO to reduced graphene oxide (RGO) to form a first network, thereby obtaining a RGO / SA / PEG mixed sol;
[0113] S4, soaking the mixed sol in a 3wt% calcium chloride (CaCl2) solution to form a second network by cross-linking SA with calcium ions to obtain RGO / CA / PEG gel;
[0114] S5. Place the above gel in an oven at 60° C. and dry for 12 h to finally obtain the desired product.
[0115] For the convenience of comparison, the experimental results are listed in Table 1.
[0116] [Comparative Example 1]
[0117] This embodiment provides a composite phase change material using double network encapsulation, which includes the following components by weight: 100 parts of PEG-6000; 20 parts of SA; 7 parts of GO; 7 parts of VC; and 2 parts of aluminum adipate.
[0118] The viscosity of SA is 5000 mPa·s, and the pH value of its 1% aqueous solution is 6-8.
[0119] GO has a thickness of 1-2 nm, a diameter of 15-20 μm, and a specific surface area of 300-350 m 2 / g, and the carbon content accounts for 51-55%.
[0120] The preparation method of the composite phase change material using dual network packaging in this embodiment includes the following steps:
[0121] S1. GO was dispersed in 50 ml of deionized water, magnetically stirred at room temperature for 8 h, and then ultrasonically exfoliated at 400 W for 16 h to obtain a stable GO dispersion for use;
[0122] S2, adding phase change material, SA, GO and aluminum adipate into GO dispersion, stirring mechanically at 80°C and 500 r / min for 3 h to obtain GO / SA / PEG sol;
[0123] S3, adding VC to the above sol, stirring at room temperature until uniformly dispersed, and then placing it in a vacuum oven at 80°C for 6 hours to fully reduce GO to reduced graphene oxide (RGO) to form a first network, thereby obtaining a RGO / SA / PEG mixed sol;
[0124] S4, soaking the mixed sol in a 3wt% calcium chloride (CaCl2) solution to form a second network by cross-linking SA with calcium ions to obtain RGO / CA / PEG gel;
[0125] S5. Place the above gel in an oven at 60° C. and dry for 12 h to finally obtain the desired product.
[0126] For the convenience of comparison, the experimental results are listed in Table 1.
[0127] Table 1
[0128]
[0129] It can be seen from Table 1 that the content of thermal conductive filler and GO will affect the thermal conductivity of the material. In the present invention, Example 4 shows good thermal performance (ΔHm=143.1J / g), high thermal conductivity (1.50W / m·K) and strong packaging ability (maintained at 80°C for 30 minutes, there is no leakage of phase change material).
[0130] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention; although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A composite phase change material using double network packaging, characterized in that: By weight, it includes the following components: Phase change material 100 parts; Sodium alginate (SA) 20 parts; 1 to 9 parts of graphene oxide (GO); L-ascorbic acid (VC) 1-9 parts; 1 to 5 parts of thermal conductive filler; 1 to 3 parts of nucleating agent.
2. The composite phase change material using double network packaging according to claim 1, characterized in that: The phase change material is one of polyethylene glycol 2000 (PEG-2000), polyethylene glycol 4000 (PEG-4000), polyethylene glycol 6000 (PEG-6000), or a combination of two or more thereof.
3. The composite phase change material using double network packaging according to claim 1, characterized in that: The viscosity of the SA is 5000 mPa·s, and the pH value of its 1% aqueous solution is 6-8.
4. The composite phase change material using double network packaging according to claim 1, characterized in that: The GO has a thickness of 1-2 nm, a diameter of 15-20 μm, and a specific surface area of 300-350 m 2 / g, and the carbon content accounts for 51-55%.
5. The composite phase change material using double network packaging according to claim 1, characterized in that: The molecular weight of VC is 176.12 g / mol, and the density at 20°C is 1.65 g / cm 3 .
6. The composite phase change material using double network packaging according to claim 1, characterized in that: The thermal conductive filler is one of aluminum oxide, aluminum nitride, and silicon micropowder, or a combination of two or more thereof.
7. The composite phase change material using double network packaging according to claim 1, characterized in that: The nucleating agent is one or a combination of two or more of sodium succinate, aluminum adipate and sodium cinnamate.
8. A method for preparing a composite phase change material using double network packaging, characterized in that: The steps include: S1. GO was dispersed in 50 ml of deionized water, magnetically stirred at room temperature for 8 h, and then ultrasonically exfoliated at 400 W for 16 h to obtain a stable GO dispersion for use; S2, adding phase change material, SA, GO, thermal conductive filler and nucleating agent into GO dispersion, stirring mechanically at 80°C and 500 r / min for 3 h to obtain GO / SA / PEG sol; S3, adding VC to the above sol, stirring at room temperature until uniformly dispersed, and then placing it in a vacuum oven at 80°C for 6 hours to fully reduce GO to reduced graphene oxide (RGO) to form a first network, thereby obtaining a RGO / SA / PEG mixed sol; S4, soaking the mixed sol in a 3wt% calcium chloride (CaCl2) solution to form a second network by cross-linking SA with calcium ions to obtain RGO / CA / PEG gel; S5. Place the above gel in an oven at 60° C. and dry for 12 h to finally obtain the desired product.
Citation Information
Patent Citations
Double-network phase change aerogel and preparation method thereof
CN111187598A
Composite phase change material for rapidly reducing smoke temperature of electronic cigarette, preparation method of composite phase change material and electronic cigarette
CN113174238A
Dual-network heat-conducting porous aerogel energy storage material as well as preparation method and application thereof
CN115260995A
Preparation method of phase change material with energy storage and composite network structure
CN117089326A
Preparation method of phase change heat storage and electrochemical energy storage aerogel
CN117577460A